2012
DOI: 10.1105/tpc.111.094912
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Crop Yields with Plant Steroids

Abstract: Plant sterols and steroid hormones, the brassinosteroids (BRs), are compounds that exert a wide range of biological activities. They are essential for plant growth, reproduction, and responses to various abiotic and biotic stresses. Given the importance of sterols and BRs in these processes, engineering their biosynthetic and signaling pathways offers exciting potentials for enhancing crop yield. In this review, we focus on how alterations in components of sterol and BR metabolism and signaling or application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
190
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(205 citation statements)
references
References 178 publications
9
190
0
6
Order By: Relevance
“…Similarly Prasad et al (2006) stated that exposure of sorghum plants to heat stress decreased the plant height due to reduction in shoot growth. There was an increase in plant height, leaf area and fresh and dry weight of L. chinensis plants by the treatment of BR (Table 2), which indicated that BR exerted positive effects on physiological processes and responses including cell division and differentiation and further improved the photosynthetic activity (Vriet et al, 2012). The results of our study are in agreement with Nassar (2004), who perceived the increase in plant height and fresh weight of banana by the treatment with BR.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly Prasad et al (2006) stated that exposure of sorghum plants to heat stress decreased the plant height due to reduction in shoot growth. There was an increase in plant height, leaf area and fresh and dry weight of L. chinensis plants by the treatment of BR (Table 2), which indicated that BR exerted positive effects on physiological processes and responses including cell division and differentiation and further improved the photosynthetic activity (Vriet et al, 2012). The results of our study are in agreement with Nassar (2004), who perceived the increase in plant height and fresh weight of banana by the treatment with BR.…”
Section: Discussionsupporting
confidence: 82%
“…Brassinosteroids (BRs) are steroidal hormones that are essential for growth and development of plants. A large number of physiological processes and responses has been known to be altered by BRs such as cell division and differentiation, functioning of stomata, photosynthesis, respiration as well as ion transport (Divi and Krishna, 2009;Vriet et al, 2012). Reports have indicated that BR induces heat stress tolerance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Plant height and cell elongation are also regulated by brassinosteroids (Vriet et al, 2012). The access to a collection of 160 short-culm mutants in a near-isogenic background and with roughly mapped mutant gene locations (Druka et al, 2011), in combination with in silico gene mapping using the latest barley genome resources (Mayer et al, 2011;The International Barley Genome Sequencing Consortium, 2012), enabled us to effectively discover brassinosteroid mutants by a reverse approach of phenotyping followed by genotyping.…”
Section: Discussion the Group Of Brassinosteroid-deficient Barleymentioning
confidence: 99%
“…Knowledge of the molecular mechanisms underlying the effects of the two hormones on cell elongation and division has mainly come from studies in Arabidopsis (Arabidopsis thaliana; Bai et al, 2012). Mutant-based breeding strategies to finetune brassinosteroid metabolism and signaling pathways could improve lodging behavior in modern crops (Vriet et al, 2012) such as barley (Hordeum vulgare), which is the fourth most abundant cereal in both area and tonnage harvested (http://faostat.fao.org).…”
mentioning
confidence: 99%
“…Till now, a total of 69 types have been found. These BR's belongs to a polyhydroxylated steroid hormones having active roles in stimulating the plant growth development with a wide range of functions such as response to environmental biotic and abiotic stresses namely salt and drought stress tolerance, photo-morphogenesis, thermotolerance, stomatal development, oxidative stress tolerance, cell death control, disease resistance, herbicide and pesticide tolerance (Vriet et al, 2012;Gruszka, 2013). Brassinosteroids at molecular level enhance metabolism of protein and nucleic acid and also affect gene expression pattern in plants (Khripach et al, 2000).…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 1462-1475mentioning
confidence: 99%